Synthesis of Nd-Pheophytin Complex and Its Hydrolysis into Nd-Pheophorbide from Katuk Leaves (Sauropus androgynous (L.) Merr) - Fadia Novayanti; Adhitiyawarman Adhitiyawarman; winda rahmalia (Jurnal Riset Sains dan Kimia Terapan, 2025)
Pheophorbide, as a chlorophyll derivative, has potential as a complexing ligand for heavy metals, including lanthanides. The synthesis of Nd-pheophytin complex and its more polar Nd-pheophorbide (pheophytin’s hydrolyzed product) were investigated using pheophytin isolated from Katuk’s (Sauropus androgynus L. Merr.) leaves. This study aims to determine the optimal reaction conditions and the complex characteristics. Pheophytin ligand and Nd were complexed under two different reaction conditions: room temperature and reflux at 65 °C for 10 hours. The pheophytin starting material was obtained by preparative thin-layer chromatography (PTLC), yielding 0.02 g. UV-vis analysis revealed characteristic absorption bands at 404 nm (Soret band) and 666 nm (Q band) in methanol, while FTIR spectra confirmed the presence of functional groups corresponding to pheophytin. The Nd-pheophytin complex formation was indicated by hypsochromic shifts in UV-vis spectra, suggesting the Nd³⁺ complexing. Fluorescence spectra between pheophytin and Nd-pheophytin showed distinct emission patterns, with pheophytin exhibiting peaks at 662 and 722 nm, while Nd-pheophytin displayed peaks with shoulders at 654 and 714 nm. Hydrolysis of Nd-pheophytin using 1 M NaOH at pH 10 produced Nd-pheophorbide. TLC analysis showed a decrease in the Rf value of Nd-pheophytin to Nd-pheophorbide from 0.95 to 0.43, with tailing, attributed to the higher polarity of pheophorbide. These findings confirm the successful synthesis and hydrolysis of the Nd-pheophytin complex.